THE IMPACT OF TECHNOLOGY-ACCELERATED SERVICE QUALITY ON MILLENNIAL CUSTOMER SATISFACTION ON THE SHOPEE PLATFORM - Rosi , Fathur; Ady, Sri Utami; Sayidah, Nur (Jurnal Review Pendidikan dan Pengajaran, 2024)
This study aims to analyze the influence of technology-accelerated service quality on customer satisfaction on the Shopee e-commerce platform. The service quality variables examined include response time, the presence of platform agents, transaction security, and product availability. This study uses a quantitative method with a survey approach. The research sample was taken from active Shopee users. The results of the analysis show that all four service quality variables have a positive and significant effect on customer satisfaction. Product availability was found to be the most dominant factor in influencing customer satisfaction. In addition, this study also found a new phenomenon where customers not only act as consumers but can also act as platform agents, thus changing the traditional paradigm in determining distribution locations. The implications of this study are the importance for e-commerce companies to continue to improve service quality, especially in terms of product availability and responsiveness. In addition, companies can utilize the potential of platform agents to expand market reach.